Examining Dewi Sartika's educational concept: Exploring the meaning behind her struggle and inspiration for contemporary education - Widyaningsih, Sri Wahyu; Kuswandi, Dedi (Journal of Research in Instructional, 2023)
This research examines the concept of education according to Dewi Sartika, the challenges faced, the support received, and the relevance of the education concept by current conditions. The research procedure used is library research. Such investigations contribute to the advancement of science, particularly in educational practice. The research results show that Dewi Sartika is an educational pioneer who is tireless in providing access to education for women. Its holistic educational concept, which involves academic, moral, and practical skills, has helped shape individuals who are not only intellectually intelligent but also ethical and have relevant skills. In addition, his recognition of the importance of local cultural values in education has contributed to maintaining and respecting Indonesia's cultural heritage. Dewi Sartika's dedication to creating an inclusive and values-centered education system has left an important mark in the history of Indonesian education that is still remembered today.